Gastro-Cosmopolitan in Osing Coffee - Zulfikar, Fachri (HISTORIKA, 2020)
This article argues that coffee is a transnational and global project in the colonial period to the present. The dramatic expansion of coffee in this period was partly brought about by foreign colonialism, and was emulated by the osing tribe. The Osing are exposed to a new culinary culture and make a new culture that is maintained until now. The culture of drinking coffee made a new festival called "Coffee with full bread". The 'gastro-cosmopolitan' culture in Banyuwangi revealed not only the extent to which the osing tribal community was confronted with transnational forces, but this influence was truly global and not limited to the osing community. this report shows that coffee is mobilized to create its own traditional osing community heritage, while also offering a platform for creative global consumerism. With the munim Osing coffee gives the sensation of being a whole Banyuwangi community with all the twists and turns in every steeping.